The ability of prior urinary cultures results to predict future culture results in neurogenic bladder patients. Issue 8 (25th May 2018) - Clark, Roderick; Welk, Blayne
Abstract : Aims: To determine if previous urinary cultures can predict the organism and susceptibility of subsequent urinary cultures in patients with neurogenic bladder dysfunction. Methods: We retrospectively identified a sample of neurogenic bladder patients from a tertiary care urology clinic (July 2015‐July 2016). We reviewed the patient chart, and then used the electronic laboratory record to identify all urine cultures done in the 2 years prior. We identified sequential culture pairs and determined the concordance of the initial culture organism to the subsequent one and similarly the concordance of the initial culture's antibiotic resistance status to the subsequent culture's one. Results: We identified 146 people with neurogenic bladder (mostly due to spinal cord injury [ n = 61], multiple sclerosis [ n = 26], or spina bifida [ n = 25]). These individuals used primarily intermittent catheterization ( n = 69, 47%) spontaneous voiding ( n = 59, 40%), or indwelling foley catheter ( n = 31, 21%). During the previous 2‐years, 81 participants had at least two positive urine cultures and a total of 479 cultures could be examined for organism/susceptibility concordance. There was 56% concordance of bacterial species between subsequent urine cultures, and this decreased significantly with increasing time between cultures ( P = 0.02). Antibiotic susceptibility concordance was high for ciprofloxacin (77%), nitrofurantoin (79%), and trimethoprim‐sulfamethoxazole (75%), with no significant change with increasing time between cultures ( P > 0.90). Conclusions: Previous positive urine cultures can provide valuable information regarding future organism and antibiotic susceptibility in individuals with neurogenic bladder. The practise of reviewing the previous urine culture when selecting empiric therapy is likely an effective practise in this population.